Penyuluhan Perilaku Cuci Tangan Pakai Sabun (CTPS) - Nuryani, Dina Dwi; Perdana, Agung Aji; Adelita, Audrey; Putri, Delima Selviyani; Syarifah, Dinda Rachma; Meliyana, Rossy (JOURNAL OF Public Health Concerns, 2023)
Background: Clean and healthy living is something that people should implement in their daily lives. So health promotion efforts to the community are very important to prevent disease. One of the PHBS programs that can be carried out is Washing Your Hands with Soap. The focus of hand washing in the education sector is elementary school children, because children are an important component as carriers of change. Purpose: To provide education regarding Hand Washing with Soap (CTPS) behavior at Public Elementary School 3 Keteguhan, East Teluk Betung District, Bandar Lampung City so that students' knowledge increases. Method: Using lecture and question and answer methods. Results: Students focused on listening and actively asked questions about Hand washing Behavior with Soap (CTPS) material. Conclusion: The activity consisted of 2 activities, namely education about Hand Washing Behavior with Soap (CTPS) attended by 65 students and a question and answer session. Keywords: Hand Wash; Knowledge;  Student Pendahuluan: Hidup bersih dan sehat merupakan suatu hal yang seharusnya memang diterapkan dalam kehidupan sehari-hari oleh masyarakat. Maka upaya promosi kesehatan kepada masyarakat sangat penting dilakukan untuk mencegah penyakit. Salah satu program PHBS yang dapat dilakukan adalah Cuci Tangan Pakai Sabun. Fokus cuci tangan di bidang pendidikan adalah anak – anak sekolah dasar, karena anak – anak merupakan komponen penting sebagai pembawa perubahan. Tujuan: Untuk memberikan edukasi mengenai Perilaku Cuci Tangan Pakai Sabun (CTPS) di SD Negeri 3 Keteguhan, KecamatanTelukBetungTimur, Kota Bandar Lampung agar pengetahuan siswa meningkat. Metode: Menggunakan metode ceramah dan tanya jawab. Hasil: Siswa fokus mendengarkan dan aktif bertanya mengenai materi Perilaku Cuci Tangan Pakai Sabun (CTPS). Simpulan: Kegiatan terdiri dari 2 aktifitas yaitu edukasi tentang Perilaku Cuci Tangan Pakai Sabun (CTPS) dihadiri sebanyak 65 siswa dan dilakukan sesi tanya jawab.